PENGEMBANGAN BAHAN AJAR KREATIF BERBASIS GOOGLE SITES PADA PEMBELAJARAN SBDP SISWA KELAS V SD NEGERI 136 JOMPIE KECAMATAN ULAWENG KABUPATEN BONE - Muin, Awaluddin; Nur, Awal; Arifin, Muh. Ilham Hidayat Arifin (MACCA : Science-Edu Journal, 2026)
This research is a development research (R&D) with the Alessi & Trollip model which consists of three stages: Planning, Design, and Development. The objectives of this research are (1) to determine the process of developing creative teaching materials using Google Sites in SBDP learning, (2) to determine the validity and practicality of creative teaching materials based on Google Sites, and (3) to determine students' responses to creative teaching materials. In this study, creative teaching materials based on Google Sites were produced for SBDP learning. The teaching materials were developed using the Alessi & Trollip model which consists of three stages: The first stage is the planning stage where researchers conduct needs analysis and content/material analysis as a basis for development. The second stage of the Alessi and Trollip development model is the design stage including flawchart and storyboard designs. Flawchart consists of a conceptual framework for creative teaching materials, while the storyboard includes all visual elements in Google Sites. In the third stage, namely development, which consists of Product Review by Experts and Product Trials. The Product Review process by Experts was carried out by a media expert validator (alpha test) and a material expert validator (beta test), the results of media validation showed a feasibility of 90.5% (very feasible), while material validation using the Gregory technique obtained 1.00 valid (very high validity). The trial conducted in this study was a small group trial. The small group trial involved fifth grade students, with student questionnaire results of 90% (very feasible) and teacher practicality sheet results (94%). In conclusion, creative teaching materials based on Google sites have been validated and declared very suitable by experts and received positive responses from students and teachers.